The effect of oral tranexamic acid tablets and LED yellow light on melasma - Rongrong HU; Cong YE; Yang YANG (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2022)
Objective To observe the clinical effect of oral tranexamic acid tablets combined with LED yellow light in the treatment of melasma. Methods A total of 80 female patients with melasma were randomly divided into the control group and the experimental group, with 40 cases in each group. These patients in the control group were given oral tranexamic acid tablets, and those in the experimental group were given led yellow light treatment on the basis of oral tranexamic acid tablets for 20 weeks. The clinical efficacy and satisfaction rates of the two groups were compared. Results Statistical analysis showed that 24 cases were significantly effective (60.00%) were improved in the experiment group, while only 15 cases (37.50%) were significantly effective in the control group. There was significant difference in the therapeutic effect between the two groups (χ2=4.05, P<0.05). There were significant difference in the decrease of MASI score (t=2.18, P<0.05) and sactisfaction rates (χ2=9.75, P<0.05) between the two groups. Conclusion Oral tranexamic acid tablets combined with LED yellow light is an effective treatment for melasma.